Clinical aspects of gastrointestinal lymphoma - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1995)
Teguh Aryandono, Taufiq Nugroho, Ahmad Ghozali -- Aspek Minis limfoma gastrointestinal.